2016
DOI: 10.1002/gps.4483
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drugs and the risk of fall injuries, hospitalisations and mortality among older adults

Abstract: ObjectiveTo investigate whether psychotropics are associated with an increased risk of fall injuries, hospitalizations, and mortality in a large general population of older adults.MethodsWe performed a nationwide matched (age, sex, and case event day) case–control study between 1 January and 31 December 2011 based on several Swedish registers (n = 1,288,875 persons aged ≥65 years). We used multivariate conditional logistic regression adjusted for education, number of inpatient days, Charlson co‐morbidity index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 34 publications
(41 reference statements)
13
122
2
2
Order By: Relevance
“…Surprisingly, we did not find an association of falls or recurrent falls with the use of hypnotics and sedatives, antiepileptics, or narcotic analgesics. However, some studies also found no significant association between falls and the use of anxiolytics/hypnotics [46], or a weaker association with the use of hypnotics and sedatives [45] or antiepilepitcs [47]. In contrast, other studies report positive associations between falls and the use hypnotics and sedatives [12,14,47,48], opioids/narcotics [46,48] [49] or antiepileptics [46].…”
Section: 80mentioning
confidence: 85%
“…Surprisingly, we did not find an association of falls or recurrent falls with the use of hypnotics and sedatives, antiepileptics, or narcotic analgesics. However, some studies also found no significant association between falls and the use of anxiolytics/hypnotics [46], or a weaker association with the use of hypnotics and sedatives [45] or antiepilepitcs [47]. In contrast, other studies report positive associations between falls and the use hypnotics and sedatives [12,14,47,48], opioids/narcotics [46,48] [49] or antiepileptics [46].…”
Section: 80mentioning
confidence: 85%
“…Diseases of nervous system including Parkinson’s and Alzheimer’s disease are associated with cognitive impairment, visual impairment, freezing in gait, postural instability, muscle weakness and impaired balance which can lead to fall 28 29. In addition, psychotropic drugs used for treating mental disorders might increase risk of fall 30. The negative associations with dementia, diabetes and cardiovascular disorders are in contrast with expectations possibly due to cause of death coding practices.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, there are major differences in the rates of consumption of antibiotics [11,12], psychotropic drugs [13], including antidepressants [14,15], and sedative-hypnotic medications [16][17][18] between white Americans and other racial groups in the US except Native Americans. A number of studies, including meta-analyses, suggest elevated risks for mortality, including sudden cardiac death (SCD) associated with the use of various psychotropic drugs (both antipsychotics and antidepressants), as well as certain sedative-hypnotic drugs (benzodiazepines) [19][20][21][22][23][24], though firmly establishing causal links in such studies can be challenging [25]. For the case of antibiotics, recent work suggests an association between prescribing rates for certain antibiotics, particularly penicillins in the elderly, and mortality and hospitalization rates for sepsis/septicemia [26,27], with that association presumably being mediated by antimicrobial resistance [28].…”
Section: Introductionmentioning
confidence: 99%